OBSERVATIONS ON CHANGES IN THE MAJOR PROTEIN NITROGEN FRACTION OF PRAWNS AND SARDINES DURING ICE STORAGE - DEVADASAN, K; NAIR, M. RAJENDRANATHAN (Fishery Technology, 2025)
Changes in the major protein nitrogen fractions viz; sarcos p1asmic, myofibrillar and stroma have been studied in two species of prawns and in oil sardine held in ice storage. Myofibrillar proteins were observed to get denatured at a rapid rate as determined by salt extractability method. The sarcoplasmic proteins were not denatured to any considerable extent. With sardine however, the extraction of myofibrillar proteins was inhibited rather in the uniced condition itself presumably owing to the presence of free fatty acids.